Locating the stigmatisation of children born of wartime rape on a continuum of violence - Rose, Sofie (Routledge, 2025)
Children born of wartime sexual violence remain a marginalised group whose lives and needs have largely been overlooked. Over the past two decades, scholarship has emerged addressing some of the multiple issues they face. This research shows that stigmatisation is central in the children’s lives, but rarely provides a deeper definition of stigma that interrogates its structural and political dimension. Bridging feminist peace scholarship and new streams of stigma research, this article sets out to conceptualise stigmatisation as a complex form of violence that concurrently reflects and reproduces gendered power dynamics across the peace–war spectrum. Drawing on narratives by children born of war in the Central African Republic, Uganda, and Bosnia-Herzegovina, this article examines how stigmatisation materialises as different forms of ‘everyday violence’ that intersects at a personal, social, and structural level. By untangling their stories, the study shows how stigmatisation profoundly impacts the children’s experiences of peace and sustains the ‘conditions of war’ in the everyday space while perpetuating structural cycles of gender-based violence that persists in transitional and post-conflict environments. The article highlights the importance of placing the children’s perspectives at the centre when analysing stigmatisation and offers new insight on how stigma operates as violence. Worldwide Political Science Abstracts